An Approach for Personalised Product Development. (2015) - Kajtaz, Mladenko; Witherow, Blake; Usma, Clara; Brandt, Milan; Subic, Aleksandar
Abstract: Currently certain standards for consumer products are expected which are mainly based around functionality, aesthetics, ease-of-use, affordability, safety, etc. Currently, smarter products that meet the user' functional and psychological needs are in demand. This paper presents an approach that was effective in identifying and quantifying subjective requirements from customers during a design of a personalised cricket faceguard successfully translating the language of the customer into a visual representation of an artefact.